Retrospective study of cultural biases and their reflections among Korean medical students: a cultural hybridity perspective - Kyung Hye Park; Ki-Byung Lee; HyeRin Roh (Korean Journal of Medical Education)
Purpose Most of studies about racial or ethnic biases among medical students have been conducted in English-speaking developed countries. This study explores the hybridity and transformation of Korean medical students’ biases, arguing that a nation’s identity and culture are constantly in a state of ever-changing hybridity. Methods This research used a qualitative document analysis. The study participants were 600 pre-clinical medical students at two medical colleges in Korea, who enrolled in anti-bias programs and subsequently submitted self-reflection essays. Data collection focused on biases related to race, ethnicity, nationality, and medical practices as doctors. Bhabha’s cultural hybridity concepts guided the coding of the data in order to explore the hybridity and transformation of the students’ biases. Results The students presented cultural biases toward patients and doctors with ambivalence related to a person’s high socioeconomic status and open-mindedness, as well as doctors’ excellence and superiority as Korean authoritative figures. Since the students had ambivalent and complex biases toward patients and doctors, they felt unhomeliness as Korean doctors encountering international patients in Korean clinics. However, after discovering their contradictory assumptions, they transformed their unhomeliness into new hybrid identities. The students’ biases were rarely based on race but instead were based on nationality, specifically national class by national income. Conclusion Understanding the changing hybrid nature of identities and culture from a cultural hybridity perspective could help clarify medical students’ complex and changing biases and improve anti-bias education. Korean medical students’ hybridized positions suggest that anti-bias education goes beyond focusing on prestige or racism.